Low XIST expression in Sertoli cells of Klinefelter syndrome patients causes high susceptibility of these cells to an extra X chromosome - Liang-Yu Zhao; Peng Li; Chen-Cheng Yao; Ru-Hui Tian; Yu-Xin Tang; Yu-Zhuo Chen; Zhi Zhou; Zheng Li (Asian Journal of Andrology, 2023)
Klinefelter syndrome (KS) is the most common genetic cause of human male infertility. However, the effect of the extra X chromosome on different testicular cell types remains poorly understood. Here, we profiled testicular single-cell transcriptomes from three KS patients and normal karyotype control individuals. Among the different somatic cells, Sertoli cells showed the greatest transcriptome changes in KS patients. Further analysis showed that X-inactive-specific transcript (XIST), a key factor that inactivates one X chromosome in female mammals, was widely expressed in each testicular somatic cell type but not in Sertoli cells. The loss of XIST in Sertoli cells leads to an increased level of X chromosome genes, and further disrupts their transcription pattern and cellular function. This phenomenon was not detected in other somatic cells such as Leydig cells and vascular endothelial cells. These results proposed a new mechanism to explain why testicular atrophy in KS patients is heterogeneous with loss of seminiferous tubules but interstitial hyperplasia. Our study provides a theoretical basis for subsequent research and related treatment of KS by identifying Sertoli cell-specific X chromosome inactivation failure.